Beyond traditional literacy: Learning and transformative practices using ICT - Therese Keane; William F. Keane; Aaron S. Blicblau (American Management Association, 2016)
Educators, government bodies and employers have acknowledged the need for modern learners to acquire 21st century skills using information and communication technologies, to personalise student learning. Students need broader skills than the 3Rs (reading, writing and arithmetic) to operate in the 21st century. These broader skills known as the 4Cs include: creativity, communication, collaboration and critical thinking. The use of information and communication technologies is crucial in developing the 4Cs in conjunction with understanding how learning takes place. However, simply using technology does not guarantee that deep learning will occur. The use of technology needs to align and adapt with our knowledge of learning to be able to operate in a transformative space. This paper is designed to link the understandings of deep learning, 21st century skills and appropriate use of information and communication technologies to provide direction to educators who wish to lead in a technological environment of change.
Keywords: collaboration; compétences; écriture et lecture numériques; éducation